An Empirical Study on Tea Export Competitiveness in Sri Lanka: Based on Partial Least Squares Structural Equation Model (Pls-Sem) - Sachitra, K.M.V. (My University, 2016)
Export development plays an important role in promoting economic growth and development. Understanding of export competitiveness has primarily been pursued in terms of economic variables and market conditions. The study involved an investigation into the determinants of export competitiveness of tea industry in Sri Lanka and to develop a framework to enhance the competitiveness of tea industry. Quantitative research approach was used and Porter’s diamond model with some adaptations was taken as proposed model of this study. E-mail survey compromised with the structured questionnaire was used to collect primary data from the sample. Key managers of tea exporting firms were considered as the respondents. Partial least squares structural equation model (PLSSEM) was utilized to analyze the contribution of each factor on tea export competitiveness. The data obtained from the firm level survey were analyzed using Smart PLS version 2.0 statistical packages. Supported by the empirical evidences this study found out that factor conditions have the most significant influence of export competitiveness of tea industry and the second important is government support. Followed by government support, demand condition and brand loyalty have also made positive impact on export competitiveness of tea industry in Sri Lanka. While identifying important elements, results indicated that raw material, technology, physical infrastructure, information infrastructure, related industries, and firm characteristics have significant impact. Giving priority to those elements strategies should be developed to enhance competitiveness of Sri Lankan tea export. By creating favourable conditions, Sri Lanka can remain competitive position in the global tea industry for many years to come.
Keywords: Tea industry; Competitiveness; Porter’s diamond model; Partial least squares structural equation